La aplicación Wordwall como herramienta digital para el Aprendizaje de Ciencias de la Tierra con estudiantes de primer semestre de la Carrera de Pedagogía de las Ciencias Experimentales Química y Biología. - Chancay González, Yajaira Yosselin (2025)
The problem was increased by the lack of motivation in the student, therefore, through the Wordwall motion, although it is true that it was a versatile and easy-to-use tool that gave the learner the ability to promote interactive actions and educational resources through playful and attractive templates. Wordwall was useful in the educational field to create interactive activities that benefit the learning of Earth Sciences. Its main objective was to develop a user guide through the Wordwall digital platform, with activities of: flash cards, anagram, word search, crossword puzzle and labeled diagrams in the second and third unit of the Earth Sciences subject to encourage the learning of the first semester student of the Degree in Pedagogy of Experimental Sciences Chemistry and Biology. The quality, versatility and ease of use of the Wordwall digital tool makes it ideal for teachers seeking to enrich their pedagogical approach and offer a more dynamic and attractive learning experience. The research methodology was quantitative, non-practical, descriptive, basic, field, bibliographic and cross-sectional study. The population was 43 students, the technique used in the research was a questionnaire, and a survey was also used. The instrument was composed of 10 questions with their different options. Finally, 100% of respondents stated that they agree that the Wordwall tool renewed learning skills. In short, the user guide through the Wordwall digital platform was effective in involving first-semester students, by including a variety of interactive and entertaining activities, not only enriching learning methods, but also promoting initiative, autonomy and cooperation in learning. Therefore, it is recommended that students of the Degree in Pedagogy of Experimental Sciences Chemistry and Biology optimize their effectiveness and offer a more active, interactive and meaningful learning experience.